Improving prefrontal cortex function in schizophrenia through focused training of cognitive control - Edwards, Bethany G.; Barch, Deanna M.; Braver, Todd S. (Frontiers in Human Neuroscience, 2010)
Previous research has shown that individuals with schizophrenia show deficits in cognitive control functions thought to depend on the lateral prefrontal cortex (PFC), and its interactions with related regions. The current study explored the effects of instructed strategy training on improving cognitive control functioning in patients with schizophrenia. Event-related fMRI was used to test whether effects of such training were associated with changes in brain activity dynamics during task performance. Patients with schizophrenia (N=22) performed the AX-CPT cognitive control task in two-sessions, with the first occurring pre-training and second following strategy training. The training protocol emphasized direct encoding of contextual cues and updating response selection goals in accordance with cue information. A matched group of healthy controls (N=14) underwent the same protocol but were only scanned in the pre-training session. In the pre-training session, patients exhibited behavioral evidence of impaired utilization of contextual cue information, along with reduced cue-related activity – but increased activation during probe and response periods – in a network of regions associated with cognitive control, centered on the lateral PFC. Following training, this pattern of activation dynamics significantly shifted, normalizing towards the pattern observed in controls. These activation effects were associated with both clinical symptoms and behavioral performance improvements. The results suggest that focused strategy training may facilitate cognitive task performance in patients with schizophrenia by changing the dynamics of activity within critical control-related brain regions.